Differently Charged Super-Paramagnetic Iron Oxide Nanoparticles Preferentially Induced M1-Like Phenotype of Macrophages - Zhang, Wenyue; Cao, Shuwen; Liang, Shunung; Tan, Chee Hwee; Luo, Baoming; Xu, Xiaoding; Saw, Phei Er (Frontiers in Bioengineering and Biotechnology, 2020)
Macrophages are mainly divided into two phenotypes: M1-like (anti-tumoral, pro-inflammatory) and M2-like (pro-tumoral, anti-inflammatory). The more abundant M2-like phenotype of tumor associated macrophages (TAMs) has been associated with poor prognosis in various cancers, therefore, many studies have been carried out to modulate TAMs to change from an M2 to M1-like phenotype as an effective way to suppress tumor growth. Previous study indicated that the FDA-approved Ferumoxytol is an iron oxide nanoparticle that has intrinsic tumor inhibiting properties and is accompanied by the increased presence of the pro-inflammatory, anti-tumoral M1-like phenotype. Intrigued by this finding, we hypothesize that differently charged super-paramagnetic iron oxide nanoparticles (SPIONs) would have preferential differences in polarizing macrophages. Herein, we report that differently charged SPIONs have distinct preferences in the modulation of TAM phenotypes. Positively-charged SPION (S+) had the highest cellular uptake and highest macrophage polarization effect. Interestingly, although negatively-charged SPION (S-) should present charge-charge repulsion with cell membranes, they showed considerably high uptake in vitro, nevertheless presenting the highest cellular toxicity. Neutrally-charged SPION (SN) showed minimal uptake and cellular toxicity in vitro. Both S+ and S- could effectively re-polarize M2-like macrophages towards M1-like macrophages in vitro, and significantly increased the Fenton effect and chemotaxis of macrophages. When macrophages pre-treated with these SPIONs were co-injected with tumor cells to obtain a tumor xenograft, S+ and S- treated macrophages significantly induced tumor retardation, indicating the successful repolarization of tumor macrophages by these SPIONs. Taken together, we provide an insight on the importance of SPION charge in immunomodulation of macrophages.